Laparoscopic Low Anterior Resection using Endo GIA Radial Reload Stapler: early results (case series) - Mukhtar, Ramiz S.; Abdul Jabbar, Mohammed Q.; Aziz, Raid A. (Journal of the Faculty of Medicine Baghdad, 2017)
Background: Laparoscopic colectomy is performed in an increasing number of institutions as a minimally invasive treatment for benign and malignant large bowel disease. Laparoscopic rectal surgery enables more accurate visualization of the anatomical structure in the pelvic cavity for selected patients with tumors in the middle and low rectum.Objectives: To determine the early outcome of patient who underwent laparoscopic low anterior resection using radial reload stapler.Patients and methods: This is a prospective study of 8 patients with low or mid rectal cancer who underwent a laparoscopic low anterior resection between January 2017 till June 2017 at Saint Raphael hospital.Results: Eight patients underwent elective laparoscopic low anterior resection, 5 (62.5%) of them were male and 3(37.5%) were female. In 6 (75%) patients complete rectal transaction done only radial reload stapler, while the other 2 (25%) patients complete transaction couldn’t be done only by the radial reload stapler and they need one Endo GIATM (Covidien) medium thick purple stapler. There was no anastomotic leakage, no wound infection and no mortality.Conclusion: The primary results and early outcome of this study showed that laparoscopic low anterior resection using radial reload is a safe procedure without increasing the risk of anastomotic leak. Further analysis in a large series is needed to draw definitive conclusions.